Transcriptional regulation of hTREX84 in human cancer cells. - Shanchun Guo; Mingli Liu; Andrew K Godwin (PLoS ONE, 2012)
TREX (transcription/export) is a multiprotein complex that plays a key role in the transcriptional elongation and transport of mRNA from the nucleus to the cytoplasm. We previously reported the purification of the human TREX protein and found that expression of a member of this complex, p84N5 (referred to as hTREX84 or hHPR1), a RB binding protein, correlated with breast tumor size and metastasis. Here we examine the mechanisms of aberrant expression of hTREX84 in breast and ovarian cancer cells and evaluate its role in tumorigenesis. We show that ovarian tumor cells over-express hTREX84 4-fold and 10-fold compared to immortal, non-tumorigenic and primary ovarian surface epithelial cells, respectively. Reduction of hTREX84 levels by small interfering RNA result in inhibition of cellular proliferation and G(2/M) arrest. Even though we observed that hTREX84 expression was induced by treatment with a demethylation agent, 5-aza-2'-deoxycytidine (5-aza-dC), sodium bisulfite DNA sequencing and methylation specific PCR found no evidence of changes in DNA methylation in the CpG islands in the regulator region of hTREX84. We subsequently identify several transcriptional factors, including NF-κB binding sites in the hTREX84 gene promoter and demonstrate by chromatin immunoprecipation (ChIP) and site directed mutagenesis that RelA/p65 binds the NF-kB binding sites and induces hTREX84 expression. Finally, we show by immunohistochemistry (IHC) that RelA/p65 is abundantly expressed in malignant cells that aberrantly express hTREX84 indicating that RelA/p65 might play a pivotal role in regulating hTREX84 expression in cancer. Our results indicate that overexpression of hTREX84 is associated with cancer cell transformation, proliferation and may be regulated by RelA/p65.